Faktor-Faktor yang Memengaruhi Keputusan Transfer Pricing yang diambil oleh Perusahaan - Putri, Sari Yuli; Bayu, Septian (Universitas Kristen Krida Wacana, 2024)
Transfer pricing refers to the price set by parties with special relationships when conducting transactions with each other. Examples of such transactions include the provision of management services, distribution of goods, and lending. Companies often use transfer pricing practices to manage their tax obligations. The purpose of this study is to identify the factors that influence companies' decisions in implementing transfer pricing. Several independent variables examined in this study include tax burden, foreign ownership, and foreign exchange rates. Meanwhile, the dependent variable in this study is transfer pricing, which is measured through the volume of sales to related parties. Multiple linear regression analysis method is used in this study using SPSS 23 software. The research findings indicate that the significant variable in companies' decision to implement transfer pricing practices is foreign ownership. However, tax burden and foreign exchange rates do not have a significant influence on companies' decisions in implementing transfer pricing. Keywords: transfer pricing, tax burden, foreign ownership, exchange rate